2017
DOI: 10.4236/fns.2017.85038
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Camel Milk Fortified with Dates in Ice Cream Manufacture on Viscosity, Overrun, and Rheological Properties during Storage Period

Abstract: The effect of using camel milk with 2 dates types (Sokary & Al-Khalas), in 3 forms (paste, pieces, and molasses), with 2 different concentrations (5% & 10%) in the manufacturing of ice cream on its viscosity, overrun%, rheological and melting properties during storage period up to 60 days at −18˚C was studied. It was noticed that there are higher mean of viscosity values (cp) when using "Al-khalas" dates paste 5% and 10% followed by samples with "sokary" paste then samples with molasses in ice cream samples co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
8
3
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 30 publications
3
8
3
1
Order By: Relevance
“…The obtained overrun results were similar to those reported by Salem et al. (2017) and Azari‐Anpar et al. (2021).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The obtained overrun results were similar to those reported by Salem et al. (2017) and Azari‐Anpar et al. (2021).…”
Section: Resultssupporting
confidence: 91%
“…The sample CB15 had the lowest overrun value (36.21%), whereas the control sample had the highest value (42.84%). Salem et al (2017) found that the overrun values of dates-added ice cream samples produced from camel's milk were between 22.20% and 27.47%.…”
Section: Physical Propertiesmentioning
confidence: 99%
“…The increase in these parameters was due to the contribution of soluble matter to the composition of the aqueous phase and of insoluble fibers to the increase in total solids, and affected the three dimensional conformation of the hydrated biopolymers. Our results are in agreement with the findings of Salem et al (2017). Smith et al (1984) reported that an increase of the changes in arrangement of water molecules around the sugar molecules were able to bring about changes in water absorption and increase the viscosity.…”
Section: Proximate Compositionsupporting
confidence: 93%
“…If protein is dissolved into the water phase, the hydrophobic part (side chain) will have an affinity to interact with the oil phase part of the interface, therefore droplets of oil can be adjacent to the water phase. This interaction will form hydrogen bonding between molecules of water with gelatin or bonds among gelatin molecules, which can then form a web and entrap the liquid to acquire an elastic and solid phase [25,26]…”
Section: Emulsion Stabilitymentioning
confidence: 99%